PENINGKATAN KETERAMPILAN MENCERITAKAN KEMBALI ISI TEKS BIOGRAFI MENGGUNAKAN MEDIA WAYANG - Yulianti, Wiwin; Syam, Christanto; Saman, Sisilya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research was to find outâ€Wayang Kardusâ€ as teaching media hekp X TKJ students of SMKn! Rasau Jaya in academic year 2017/2018 improve their speaking ability, especially retelling a biography text. This research implemented classroom action reseach in which the intruments used were test, IPKG 1,IPKG 2, students activity guidelines and dokumentation. This classroom action research was conducted in three cycles. In cycle 1, the data revealed 3 student got very least active, 22 least active, 3 active enough,, and 7 active. The students everage score both linguistics 6,4% and nonlinguistic 6,35%, final score was 65,42%. Based on the IPKG 1 and IPKG 2, the teacher got 48 in activity assessments, categirized as good enough.in cycle II, 13 students got active enough, 16 active and 6 very active. Students linguistic aspect hasÂ  improved to 7,91% and nonlinguistic aspect was 7,80%. The students rate was 74,28%. Teacher assessments based on the IPKG 1 guidelines have improved to 64 and IPKG 2Â  was 65, categirized as good, Cycle III revealed a better improvement. There were 13 students were active enough, 13 active and 19 got very avtive. From the aspect of lingustich, the score was 8,54% and from the aspect ofÂ  nonlinguistich was 8,44%. Â Key words: Media, Speaking, Wayang Kardus,